Strength, deformability and toughness of uncrosslinked fibrin fibers from theoretical reconstruction of stress-strain curves. (December 2021) - Maksudov, Farkhad; Daraei, Ali; Sesha, Anuj; Marx, Kenneth A.; Guthold, Martin; Barsegov, Valeri
Abstract: Structural mechanisms underlying the mechanical properties of fibrin fibers are elusive. We combined tensile testing of uncrosslinked fibrin polymers in vitro and in silico to explore their material properties. The experimental stress ( σ ) – strain ( ε ) curves for fibrin fibers are characterized by elastic deformations with a weaker elastic response for ε <160% due to unraveling of αC tethers and straightening of fibrin protofibrils, and a stronger response for ε >160% owing to unfolding of the coiled coils and γ nodules in fibrin monomers. Fiber rupture for strains ε >212% is due to dissociation of the knob-hole bonds and rupture of D:D interfaces. We developed the Fluctuating Bilinear Spring model to interpret the σ − ε profiles in terms of the free energy for protofibril alignment Δ G 0 = 10.1–11.5 k B T, Young's moduli for protofibril alignment Y u = 1.9-3.2 MPa and stretching Y a = 5.7–9.7 MPa, strain scale ε ˜ ≈ 12–40% for fiber rupture, and protofibril cooperativity m = 3.6–8. We applied the model to characterize the fiber strength σ c r ≈ 12-13 MPa, deformability ε c r ≈ 222%, and rupture toughness U ≈ 9 MJ/m 3, and to resolve thermodynamic state functions, 96.9 GJ/mol entropy change for protofibril alignment (at room temperature) and 113.6 GJ/mol enthalpy change for protofibril stretching, which add up to 210.5 GJ/mol free-energy change. Fiber elongation is associated with protofibril dehydration and sliding mechanism to create an ordered protofibril array. Fibrin fibers behave like a hydrogel; protofibril dehydration and water expulsion account for ∼94-98% of the total free-energy changes for fiber elongation and rupture. Statement of significance: Structural mechanisms underlying the mechanical properties of fibrin fibers, major components of blood clots and obstructive thrombi, are elusive. We performed tensile testing of uncrosslinked fibrin polymers in vitro and in silico to explore their material properties. Fluctuating Bilinear Spring theory was developed to interpret the stress-strain profiles in terms of the energy for protofibril alignment, elastic moduli for protofibril alignment and stretching, and strain scale for fiber rupture, and to probe the limits of fiber strength, extensibility and toughness. Fibrin fibers behave like a hydrogel. Fiber elongation is defined by the protofibril dehydration and sliding. Structural rearrangements in water matrix control fiber elasticity. These results contribute to fundamental understanding of blood clot breakage that underlies thrombotic embolization. Graphical abstract: Image, graphical abstract